Partisipasi Remaja dalam Hidup Menggereja Ditinjau dari Aspek Perkembangan Jiwa Keagamaan Remaja - Silvester Nusa; Margaretha Vinsensia Ina (Ideas Publishing, 2023)
The study background refers to the low involvement of youth in church life. Meanwhile, the Catholic youth are backbone and spearhead of the church in keeping the mission of Jesus Christ on going in this world. This study aims to identify and describe the factors that triggers the involvement and uninvolvement of the catholic youth based on their religious spirit of adolescents. Religious religionis the internal psychic ability of man in the form of beliefs in God with devotional teachings and obligations in accordance with that belief. This is a descriptive qualitative study and the result indicated that the involvement and uninvolvement of the catholic youth in church life are driven by a religious spirit, such as consecutive beliefs, emotional condition, the desire of existence, the awareness of believing and the ability to overcome doubts in having a religion.